Dsg2 Upregulation as a Rescue Mechanism in Pemphigus - Sigmund, Anna M.; Steinert, Letyfee S.; Egu, Desalegn T.; Bayerbach, Franziska C.; Waschke, Jens; Vielmuth, Franziska (Frontiers in Immunology, 2020)
In pemphigus vulgaris (PV), autoantibodies directed against the desmosomal cadherin desmoglein (Dsg) 3 cause loss of intercellular adhesion. It is known that Dsg3 interactions are directly inhibited by autoantibody binding and that Dsg2 is upregulated in epidermis of PV patients. Here, we investigated whether heterophilic Dsg2-Dsg3 interactions occur and would modulate PV pathogenesis. Dsg2 was upregulated in PV patients’ biopsies as well as in a human ex vivo pemphigus skin model. Immunoprecipitation and cell-free atomic force microscopy (AFM) experiments demonstrated heterophilic Dsg2-Dsg3 interactions. Similarly, in Dsg3-deficient keratinocytes with severely disturbed intercellular adhesion Dsg2 was upregulated in the desmosome containing fraction. AFM revealed that Dsg2-Dsg3 heterophilic interactions showed binding frequency, strength, Ca2+-dependency and catch-bond behavior comparable to homophilic Dsg3 or Dsg2 interactions. However, heterophilic Dsg2-Dsg3 interactions had a longer lifetime compared to homophilic Dsg2-Dsg2 interactions and PV autoantibody-induced direct inhibition was significantly less pronounced for heterophilic Dsg2-Dsg3 interactions compared to homophilic Dsg3 interactions. In contrast, a monoclonal anti-Dsg2 inhibitory antibody reduced heterophilic Dsg2-Dsg3 and homophilic Dsg2-Dsg2 binding to the same degree and further impaired intercellular adhesion in Dsg3-deficient keratinocytes. Taken together, the data demonstrate that Dsg2 undergoes heterophilic interactions with Dsg3, which may attenuate autoantibody-induced loss of keratinocyte adhesion in pemphigus.